ANALYSIS OF PREFIXES AND SUFFIXES IN OBSTETRICS-GYNECOLOGICAL WORDS IN UZBEK AND ENGLISH (American Journal of Interdisciplinary Research and Development, 2025)
This article presents the ideas that word formation is the formation of a new meaningful word by adding an affix to the root morpheme, that the main task of word formation is to increase the new vocabulary of the language, and that the greater the vocabulary of the language, the more fluent and colorful the speaker's speech will be. This research used the descriptive qualitative method. Contrastive analysis is used to describe the result of the study between English and Uzbek suffixes that had been compared.